A case study of community-led edible landscape revitalization in post-industrial Shenyang, China - Yu, Hang; Mohd Yunos, Mohd Yazid; Saidon, Mohd Nazri; Hussain, Mohd Amirul (Routledge, 2025)
This study critically examines how community-led edible landscapes intersect with processes of memory-making and spatial regeneration in post-industrial Shenyang, China. Rather than presuming their inherent social or ecological benefit, the research investigates how these informal practices negotiate the tensions between urban redevelopment, memory politics, and governance ambiguity. Drawing on a qualitative case study approach—including participant observation, semi-structured interviews, and spatial documentation—the findings show that while edible landscapes can revitalise neglected spaces and evoke industrial memory, they also face instability, informal governance, and socio-environmental risks. The study argues that such landscapes operate as contested sites where care, memory, and precarity converge, offering nuanced insight into the limits and possibilities of edible urbanism in the context of post-industrial transformation.